2015
DOI: 10.4025/actascibiolsci.v37i2.23015
|View full text |Cite
|
Sign up to set email alerts
|

<b>Environmental and dam effects on cannibalism in Wistar rat litters

Abstract: ABSTRACT. The factors related to cannibalistic behavior of dams in a Wistar rat colony are identified and analyzed. The maternal genetic effects were tested as a random effect by the method of generalized linear models. The season at parturition, the dam´s age at parturition and the density of the room at parturition were tested as fixed effects, whereas the litter size at birth was tested as a co-variable. The genetic effect of the dam was significant for the number of cannibalized pups. Although the season a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, the genetic correlation (rg 0.77) between LS and CAN suggests that selection for increasing litter size may lead to higher maternal cannibalism incidence in the evaluated Wistar rat population. Aggressive dam behavior towards offspring may be related to both factors, since CAN is an inheritable trait according to the genetic variability found (h 2 = 0.07), as reported by Perrigo et al (1993) and Poikonen et al (2008), in addition to environmental factors (Korpela et al, 2010, Weber et al, 2013, Tarôco et al, 2015. Korpela et al (2010) reported that increasing density populations can result in higher infanticide rates in a vole's population.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…On the other hand, the genetic correlation (rg 0.77) between LS and CAN suggests that selection for increasing litter size may lead to higher maternal cannibalism incidence in the evaluated Wistar rat population. Aggressive dam behavior towards offspring may be related to both factors, since CAN is an inheritable trait according to the genetic variability found (h 2 = 0.07), as reported by Perrigo et al (1993) and Poikonen et al (2008), in addition to environmental factors (Korpela et al, 2010, Weber et al, 2013, Tarôco et al, 2015. Korpela et al (2010) reported that increasing density populations can result in higher infanticide rates in a vole's population.…”
Section: Discussionmentioning
confidence: 60%
“…Mattaraia and Moura (2012) reported that the mating system (monogamous and polygamous) adopted in the reproductive management of Wistar rats can influence the pup mortality and calving intervals. Moreover, Tarôco et al (2015) reported that genetic and environmental factors are related to dam's behavior and may influence maternal cannibalism by reducing the number of weaned animals in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%